Evaluation of radon, radium and gamma radiation at the environmental preservation area of Passaúna river, Brazil - Aline Cristina Martin; Sergei Anatolyevich Paschuk; Janine Nicolosi Corrêa; Flávia Del Claro; Oderson Antônio de Souza Filho (Brazilian Journal of Radiation Sciences, 2021)
The objective of this research was to evaluate the levels of natural radiation in the Environmental Protection Area (APA) of the Passaúna River (Campo Largo region) in the state of Paraná, Brazil. Gamma radiation measurements were obtained with the gamma spectrometer, and for the measurements of radium and radon concentrations in soil and water the AlphaGUARD monitor and its accessories were used. Until the present time, 4 water samples from Passaúna’s River, 2 well water samples from the region, 2 sample of a secondary lake and 4 soil samples. The results show that the gamma spectrometric measurements found values ranging from 0.052 to 0.204 μSv / h. However, the results of the radon concentrations in the soil were significant, since the values obtained varied from 110 ± 1.30 kBq/m³ to 9 ± 0.80 kBq/m³, which results can be compared with the radon and radio measurements obtained in the wells water, which indicated values higher than the national limit of 0.5 Bq/L, established by the Brazilian Ministry of Health, and the World Health Organization. The values in the lake water were lower the limits. More measurements are needed to map the region to understand the radiation levels and to correlate water and soil measurements with the geological features of the place.